Expression and functional analysis of CsA-IPT5 splice variants during shoot branching in Camellia sinensis - Zhang, Liping; Wang, Donghui; Zhang, Lan; Fu, Jianyu; Yan, Peng; Ge, Shibei; Li, Zhengzhen; Ahammed, Golam Jalal; Han, Wenyan; Li, Xin (Frontiers in Plant Science, 2022)
Alternative splicing (AS) is a process by which several functional splice variants are generated from the same precursor mRNA. In our recent study, five CsA-IPT5 splice variants with various numbers of ATTTA motifs in the untranslated regions (UTRs) were cloned. Meanwhile, their transient expression, as well as the expression and functional analysis in the two shoot branching processes were studied. Here, we examined how these splice variants regulate the other three important shoot branching processes, including the spring tea development, the distal branching of new shoots, and the shoot branching induced by 2,3,5-triiodobenzoic acid (TIBA) spraying, and thus unraveling the key CsA-IPT5 transcripts which play the most important roles in the shoot branching of tea plants. The results showed that the increased expression of 5′ UTR AS3, 3′ UTR AS1 and 3′ UTR AS2 could contribute to the increased synthesis of tZ/iP-type cytokinins (CKs), thus promoting the spring tea development. Meanwhile, in the TIBA-induced shoot branching or in the distal branching of the new shoots, CsA-IPT5 transcripts regulated the synthesis of CsA-IPT5 protein and CKs through transcriptional regulation of the ratios of its splice variants. Moreover, 3′ UTR AS1 and 3′ UTR AS2 both play key roles in these two processes. In summary, it is revealed that 3′ UTR AS1 and 3′ UTR AS2 of CsA-IPT5 might act as the predominant splice variants in shoot branching of the tea plant, and they both can serve as gene resources for tea plant breeding.